Pengaruh Lama Fermentasi Fruitghurt Pisang Cavendish (Musa acuminate cavendish) dengan Starter Lactobacillus Bulgaricus dan Streptococcus Thermophilus terhadap Kualitas Mutu Sediaan Fruitghurt - St. Rahmatullah; Khafid Mahmub (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2019)
Lactobacillus bulgaricus and Streptococcus thermophillus are common used in fruitghurt manufacture. The purpose of the study was to develop the processing of cavendish bananas into fruitghurt that has the physical properties which favored by selected panelist in accordance with the standard quality of SNI Yoghurt. Further more fermented fruitghurt was ecaluated according to SNI Yoghurt, 2009. The result showed that the organoleptic, the determination of total fruitghurt solids, fatty acid, protein content, total BAL count and stability assay of all treatment samples were have proper base on SNI Yoghurt. Fruitghurt with 24 hours fermentation produced the best quality of fruitghurt and favorited by selected panelist.